Dividend policy of the Jakarta Stock Exchange listed manufacturing company and the underlying factors - Farah Chintya Benyadi; Andrianantenaina Hajanirina; Mila Austria Reyes (President University Press, 2022)
The purpose of this study is to analyze whether profitability, liquidity, leverage and firm size affect dividend policy. Dividend provides riskless revenue for shareholders and though according to the theory, dividend, is irrelevant to firm value. Dividend policy is measured by dummy variable, and the underlying factors including profitability which using return on asset to be measured, liquidity that using current ratio, leverage which using total debt to total asset ratio while log natural of total asset is used as measurement of the firm size. Data collection is using purposive sampling with total sample of 61 companies from manufacturing sector companies listed on Indonesia Stock. This study is using binary logistic regression with 299 sample size. The outcome of this study present that dividend policy is significantly associated with profitability and firm size yet have no significantly correlated with liquidity and leverage of the company.